PENGARUH PESAN DAKWAH AKUN YOUTUBE PEMUDA TERSESAT TERHADAP PERILAKU BERAGAMA PENONTONNYA : Survei Kepada Subscriber Akun Youtube Pemuda Tersesat. - Dafin Rullyansyah Pradana (2023)
The emergence of many da'wah accounts on the internet does not guarantee that what they teach is correct and in accordance with the Islamic religion as it should be. One of the da'wah accounts that is viral, especially among young people, is Pemuda Tersesat by Habib Ja'far on YouTube with the concept of comedy da'wah which has Coki and Muslim as the hosts. This study purpose to find out how much influence the da'wah messages delivered by the Pemuda Tersesat's Youtube account have on the religious behavior of the audience, especially the subscribers of Pemuda Tersesat which are carried out through YouTube social media. The theory used in this study is the Elaboration Likelihood Model using an explanatory quantitative approach that uses surveys as a data collection method for 688,000 subscribers of Pemuda Tersesat's Youtube account with a sample size of 100 respondents. The technique of analyzing the effect of variable X on variable Y using the regression test and test the coefficient of determination obtains positive results that there is an influence between variable X on variable Y of 80.6% and the rest is influenced by other factors outside of the research conducted this time, this means the da'wah message what Pemuda Tersesat did in the Elaboration Likelihood Model theory contains a strong argument. The results of the correlation test obtained a result of 0.821, there was a very strong relationship between the two variables and the hypothesis test found that H0 was rejected and Ha was accepted, meaning that there is a significant influence between the da'wah messages from the Pemuda Tersesat account on Youtube on the religious behavior of the audience. The conclusion in this study is that there is a significant influence between the da'wah message on the religious behavior of the Pemuda Tersesat audience and in the Elaboration Likelihood Model theory the audience uses the peripheral route to understand the contents of the message conveyed by Pemuda Tersesat.